Adolescent mothers’ experiences in the feeding care of their children - Taglietti, Roberta Lamonatto; Teo, Carla Rosane Paz Arruda; Ferretti, Fátima (Saúde (Santa Maria), 2019)
Objective: Understanding the meanings produced by adolescent mothers who experience the feeding care of their children. Methods: Qualitative research carried out with nine primiparous teenagers. Semi-structured interview and thematic content analysis were applied. Results: From the analysis, meaning categories of feeding care emerged, related to insecurity, responsibility, pleasure, satisfaction, frustration, dissatisfaction, impatience, burden, and losses. Feeding care implies insecurity and great responsibility to the mother, who recognizes it as a determinant of her child’s health and an indicator of maternal competence. There also emerged senses of pleasure and satisfaction, frustrations and dissatisfactions, derived from food acceptance or rejection by the child. Senses of impatience and burden were produced, too, as preparing and offering food to the child requires time and patience. Taking responsibility for this care is assigned to the sense of losses for the teenagers, who drop out of school and move away from their social groups. Conclusions: It is concluded that experiencing motherhood in adolescence and properly feeding the child is a task surrounded by expectations and uncertainties that require a special attention at this life stage, when self-care is not consolidated, yet.